Diseño de productos pedagógicos para la asignatura de Ciencias Naturales en la Unidad Educativa González Suárez - Pamela Cecibel Flores Medina (2024)
The González Suárez Educational Unit is dedicated to offering primary and secondary education with a focus on the integral formation of its students. However, a limited supply of didactic materials for teaching Natural Sciences has been identified, which has an impact on the ability of teachers to implement innovative educational strategies and negatively affects the academic performance of students. This project is based on the need to improve the quality of Natural Sciences teaching by introducing materials that promote interactive and meaningful learning. Currently, the learning experience is unappealing to students, impacting on their interest and academic performance. Therefore, it is essential to design and develop pedagogical products that respond to current educational needs. For the development of this project, the Design Thinking methodology was used. Through this, a pedagogical product was designed that integrates the teaching of the periodic table with solar system topics, thus capturing students' attention and improving their understanding of these concepts. The research revealed that both students and teachers show great interest in practical and interactive teaching methods, highlighting the effectiveness of the newly designed materials. The proposal of this research focuses on implementing the pedagogical products designed in the subject of Natural Sciences at the González Suárez Educational Unit. This initiative seeks to improve academic performance and foster a genuine interest in science, contributing to the development of meaningful and lasting learning.